A real-world comparative analysis of carfilzomib and other systemic multiple myeloma chemotherapies in a US community oncology setting. (January 2019) - Rifkin, Robert M.; Medhekar, Rohan; Amirian, E. Susan; Aguilar, Kathleen M.; Wilson, Thomas; Boyd, Marley; Mezzi, Khalid; Panjabi, Sumeet
Background: Most multiple myeloma (MM) patients ultimately progress, with remission duration decreasing after first relapse. Recently, novel agents have been approved for the treatment of relapsed MM. There is a paucity of real-world data on these treatments. We sought to compare time to next treatment (TTNT) in MM patients in their second line of therapy (LOT2), treated with common proteasome inhibitor (PI)-based triplets. Methods: Adult MM patients who received carfilzomib (K) between 1 November 2013 and 29 February 2016 at US Oncology Network (USON) clinics utilizing iKnowMed™ electronic health records (EHRs) were identified. Patients were included if they were ⩾18 years of age, not enrolled in clinical trials, had ⩾2 visits at a USON clinic and received LOT2 regimens consisting of: K+lenalidomide with steroid (KRd), bortezomib+lenalidomide with steroid (VRd), or bortezomib+cyclophosphamide with steroid (VCyd). TTNT was estimated from LOT2 initiation to LOT3 initiation using the Kaplan–Meier method, and hazard ratios (HRs) were estimated using Cox modeling. Results: A total of 718 patients received a K-containing regimen sometime during their MM treatment (LOT1 to LOT5). Of these, 156 patients received: KRd ( n = 112; 71.8%), VRd ( n =27; 17.3%), or VCyd ( n = 17; 10.9%). Baseline characteristics were similar between groups (mean age: 64.8 years; 58% male). Median TTNT was longest for KRd [25.3 months; 95% confidence interval (CI): 19.71–NR], versus VRd or VCyd (VRd median TTNT: 10.2 months, 95% CI: 4.24–12.71; VCyd: 6.5 months, 95% CI: 3.02–12.78; log-rank p < 0.0001). The adjusted HR for KRd was 0.19 (95% CI: 0.11–0.37), compared with VRd. Conclusions: Considering the real-world nature of these data, the median TTNT observed with KRd was relatively consistent, with progression-free survival (PFS) for KRd observed in the phase III ASPIRE trial (median PFS: ITT population = 26.3 months; LOT2 = 29.6 months). Patients who received KRd at first relapse had significantly longer TTNT, compared with those on VRd or VCyd, confirming the value of KRd as an important treatment option for relapsed MM.